New performance of biosensor technology for Alzheimer's disease drugs: in vitro comparison of tacrine and 7-methoxytacrine - Pohanka, Miroslav; Kuca, Kamil; Kassa, Jiri (Neuro endocrinology letters, 2008)
Two drugs were tested using electrochemical biosensor with immobilized acetylcholinesterase (AChE). The first was commercialized drug tacrine (known also as Cognex) used for treatment of cognitive manifestation of Alzheimer\'s disease (AD). The second one was its 7-methoxy derivate (7-MEOTA) that has not been marketed. We determined the IC50 (6.67+/-0.92)x10-7 M for tacrine and (1.66+/-1.43)x10-9 M for 7-MEOTA. In this in vitro study, 7-MEOTA acts as stronger inhibitor of AChE and in this way could be more favorable for treatment of cognitive manifestation of AD. Our study shows that biosensor technology could be used as a quick and cheap tool for testing of promising AChE inhibitors (AD drug candidates).
Keywords: kinetika; algoritmy; enzymy imobilizované; Acetylcholinesterase; biosenzitivní techniky; Enzymes, Immobilized; cholinesterasové inhibitory; acetylcholinesterasa; Algorithms; takrin; Tacrine; Cholinesterase Inhibitors; Alzheimer Disease; Biosensing Techniques; nootropní látky; Electrochemistry; Humans; Kinetics; Nootropic Agents; Alzheimerova nemoc; elektrochemie; lidé